Send Flowers : A magical realism exploration of love and loss - Buchanan, Emily ([Place of publication not identified] : Park Row, 2025)
"Fiona, better known as eco-influencer @FoliageFifi, hasn't left her apartment since her boyfriend, Ed, died. It's easy to self-isolate when your heart's shattered and the planet you've spent your whole life trying to save is dying right outside your window. But when a houseplant randomly appears on her doorstep with an anonymous note, Fiona feels a flicker of hope--it's not just any plant; it's Ed's favorite. Thinking it's a sign, Fiona pours Ed's ashes into the soil, only to wake up to find the plant has vibrantly flowered. And can...talk? There's only one logical explanation: Ed is back. This time as a houseplant. As Fiona knows all too well, plants have needs--sunlight, water and fresh air--all of which she can't adequately provide from her dark, stuffy apartment. Intent on keeping Ed alive, Fiona slowly ventures back out into the world, the plant's voice and budding flowers her guiding compass. But when Ed becomes more demanding in his botanical needs, urging her toward the people and places that left her scarred, Fiona realizes that preserving Ed's life could mean risking her own. How far will she go to keep him blooming?"--.
new book 2025 summer.
Keywords: Grief; House plants; Psychological fiction; Internet personalities; Loss (Psychology); Environmentalism